After partnerships, neighbourhoods and advanced status… Who fears the Union for the Mediterranean? - Escribano, Gonzalo; Rodríguez, Laura (Papeles de Europa, 2010)
The Union for the Mediterranean (UfM) is the current framework for political, economic and cultural relations between the EU and the Mediterranean Partner Countries (MPCs). This article analyses its evolution study, from its inception to its finals design, approved in Marseille in 2008. It also addresses the UfM’s eventual results, concluding that it is necessary to make a substantial progress in the Euro- Mediterranean relations by adding new relevant incentives to MPC’s, while maintaining the spirit of the Barcelona Process.
Keywords: Barcelona Process; Unión for the Mediterranean; Mediterranean Partner Countries; EU foreign policy